1984
DOI: 10.1002/1097-4679(198407)40:4<1033::aid-jclp2270400428>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Application of the four-subtest WAIS-R short form with an older clinical sample

Abstract: Investigated the validity of the Arithmetic + Vocabulary + Picture Arrangement + Block Design subtest combination as an estimate of the WAIS‐R Full Scale IQ in a smaple of 55 elderly patients. The correlation between the short‐form IQ and the WAIS‐R Full Scale IQ was highly significant, r(53) = 0.95, p < 0.001. A pairwise t‐test computed between the mean IQs for the two forms was nonsignificant, t(54) < 1. Approximately one‐fourth of the Ss showed changes in intelligence classification levels when the short fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Roth et al concluded that Silverstein's short forms provide only a rough, positively biased estimate of FSIQ in clinical settings. Ryan, Georgemiller, and McKinney (1984) evaluated SF4 in a sample of 55 elderly patients (54 males, 1 female). Although 27% of the subjects showed changes in IQ classification, the correlation between short form IQ and WAIS-R FSIQ was highly significant and mean IQ's for the two forms were nonsignificant.…”
mentioning
confidence: 99%
“…Roth et al concluded that Silverstein's short forms provide only a rough, positively biased estimate of FSIQ in clinical settings. Ryan, Georgemiller, and McKinney (1984) evaluated SF4 in a sample of 55 elderly patients (54 males, 1 female). Although 27% of the subjects showed changes in IQ classification, the correlation between short form IQ and WAIS-R FSIQ was highly significant and mean IQ's for the two forms were nonsignificant.…”
mentioning
confidence: 99%
“…For example, classifying the subjects in this study on the basis of their two-, three-, and four-subtest estimated IQs resulted in misclassification rates of 37%, 31%, and 24%, respectively. Other investigators studying different WAIS–R short forms (e.g., Ryan, Georgemiller, & McKinney, 1984) have reported similar rates of misclassification, a phenomenon that clearly derives from the measurement error inherent in the instruments. Kaufman et al (1991) have recommended that an estimated IQ never be used to classify an individual according to level of intelligence; rather, the score obtained should be reported and unambiguously labeled as an estimated IQ, ideally with an associated confidence interval.…”
Section: Discussionmentioning
confidence: 83%
“…In a study, the correlation between four subtests short form and WAIS-R Full-Scale IQ reported highly significant (r (53)= .95). According to this result, the four subtests short form appear to have clinical utility as a screening device to identify patients with atypical cognitive functioning (Ryan, Georgemiller, & McKinney, 1984). Four subtests of WASI-R were employed to control the effect of intelligence on two groups' performances.…”
Section: Youth Psychopathic Traits Inventory (Ypi)mentioning
confidence: 99%